Document Management Techniques & Technologies - Sathiadas, Joseph P.; Wikramanayake, G.N. (My University, 2003)
Electronic Document Management System (EDMS) is a rapidly developing technology and is considered as the solution for organizations that needs a way to manage the information efficiently. EDMS applications focus on the control of electronic documents throughout their entire life cycle, from creation to eventual archiving. Its functions include document creation, storage and retrieval, management, version control, workflow and multiple delivery formats. Document management is not a single entity or technology, but rather a combination of elements. It is the use of information and different users in a business process, combined with the technology that permits the interaction. The technologies that make up the EDMS are categorized into distinct functional groupings. We present these and describes the techniques used to electronically manage documents. We also explores the immediate future of the EDMS and conclude that having the EDMS industry is at crossroads in its own lifecycle and is made up of a highly fragmented group of products with no single integrated vendor or framework for automating the entire cradle to grave document life cycle.